Evaluation of inflammatory responses due to small interfering RNA transfer using unmodified- and mannose-modified bubble lipoplexes with ultrasound exposure in primary cultured macrophages. (September 2014) - Yoshida, Mitsuru; Kawakami, Shigeru; Un, Keita; Kono, Yusuke; Higuchi, Yuriko; Yamashita, Fumiyoshi; Hashida, Mitsuru
Abstract Development of an efficient small interfering RNA (siRNA) delivery method using non-viral carriers is necessary to determine potent therapeutic effects of RNA interference. Inflammatory responses induced by siRNA interaction with Toll-like receptors and retinoic-acid-inducible gene I protein/melanoma differentiation-associated gene 5 (RIG-I/MDA-5) are obstacles to the application of siRNAs in clinically. Here, we evaluated the effects on inflammatory responses by our siRNA delivery method using bubble lipoplexes with ultrasound (US) exposure in cultured macrophages. The effective gene suppression effects were obtained under low-toxic conditions in this siRNA transfer method. The interferon (IFN)-α after siRNA transfer using lipoplexes/bubble lipoplexes with US exposure was not detected. However, low levels of type I IFN mRNA production were induced through interaction of siRNA and cytoplasmic RIG-I/MDA-5, but not Toll-like receptors. Our findings indicate that it is possible to develop a safe and efficient siRNA delivery technique using mannosylated bubble lipoplexes and US exposure.